National Trends for Primary and Revision Lumbar Disc Arthroplasty Throughout the United States. Issue 2 (April 2018) - Saifi, Comron; Cazzulino, Alejandro; Park, Caroline; Laratta, Joseph; Louie, Philip K.; Shillingford, Jamal N.; Lehman, Ronald; An, Howard; Phillips, Frank
Study Design: Retrospective database study. Objectives: Analysis of economic and demographic data concerning lumbar disc arthroplasty (LDA) throughout the United States to improve value-based care and health care utilization. Methods: The National Inpatient Sample database was queried for patients who underwent primary or revision LDA between 2005 and 2013. Demographic and economic data included total surgeries, costs, length of stay, and frequency of routine discharge. The National Inpatient Sample database represents a 20% sample of discharges from US hospitals weighted to provide national estimates. Results: Primary LDA decreased 86% from 3059 to 420 from 2005 to 2013. The mean total cost of LDA increased 33% from $17 747 to $23 804. The mean length of stay decreased from 2.8 to 2.4 days. The mean routine discharge (home discharge without visiting nursing care) remained constant at 91%. Revision procedures (removal, supplemental fixation, or reoperation at the treated level) declined 30% from 194 to 135 cases over the study period. The mean revision burden, defined as the ratio of revision procedures to the sum of primary and revision procedures, was 12% (range 6% to 24%). The mean total cost of revisions ranged from $12 752 to $22 282. Conclusions: From 2005 to 2013, primary LDA significantly declined in the United States by 86% despite several studies pointing to improved efficacy and cost-efficiency. This disparity may be related to a lack of surgeon reimbursement from insurance companies. Congruently, the number of revision LDA cases has declined 30%, while revision burden has risen from 6% to 24%.